Antiobesity Activity of Porang Tuber Flour (Amorphophallus muelleri) in Obesity Rat Model - Sherin Isna Meiliana; Muhtadi Muhtadi (Prosiding University Research Colloquium, 2022)
Obesity is a condition in which the body experiences excess fat accumulation so that body weight is far above normal. Obesity is a risk factor for various metabolic and degenerative diseases such as cardiovascular disease, diabetes mellitus, osteoarthritis. It is necessary to reduce obesity in order to reduce the risk factors for the disease. The study aimed to determine the anti-obesity activity of porang tuber flour (Amorphophallus muelleri) in an obese rat model. A total of 25 rats were grouped into 5 groups, namely the positive group (receiving orlistat 15.6 mg/kg.BW), the negative group and 3 groups receiving porang flour doses of 100, 50, and 25 mg/kg.BW. All groups were induced on a high-fat and fructose diet for 21 days, the drug and porang flour in the form of a suspension was given for 14 days. The main data is body weight, and Lee's index which is measured every 7 days. The results showed that there was no significant difference in body weight loss between the group of animals receiving porang tuber flour and the orlistat-induced group (p>0.05). It was concluded that porang flour in this study did not have an anti-obesity effect.